Respuesta :
1. -3 - (-8) = -3 + 8 = 5 <==== Answer
2. -2 - 3 = -2 + -3 = -5
3. 1 - (-4) = 1 + 4 = 5 <===== Answer
4. 7 - (-2) = 7 + 2 = 9
Hope this helped u!!!
Have a great day :)
The following expressions have a difference of 5; A) –3 – (–8) and B) 7 – (–2).
What are equivalent expressions?
Those expressions who might look different but their simplified forms are same expressions are called equivalent expressions.
To derive equivalent expressions of some expression, we can either make it look more complex or simple. Usually, we simplify it.
The following expressions have a difference of 5;
1. -3 - (-8) = -3 + 8 = 5
2. -2 - 3 = -2 + -3 = -5
3. 1 - (-4) = 1 + 4 = 5
4. 7 - (-2) = 7 + 2 = 9
Hence, The following expressions have a difference of 5; A) –3 – (–8) and B) 7 – (–2).
Learn more about expression here;
https://brainly.com/question/14083225
#SPJ5